The determinants of travel mode choice: the case of Łódź, Poland - Wójcik, Szymon (Bulletin of Geography. Socio-economic Series, 2019)
In this study, potential factors influencing the decisions made by citizens of the city of Łódź, Poland, regarding the choice of transportation mode used in their daily travel activities were examined. In addition to a brief literature review, an empirical study was performed. Data from a previous quality-of-life study were used to enhance the scope of explanatory variables in a regression model. In order to identify the determinants of travel behaviour, binary logistic regression models were used. The results show that socio-demographic characteristics of respondents and household access to a car most influenced transport mode choices. Also, the relationship between geographic distances and subjective opinions regarding public transport were found to be statistically significant. The determinants for choosing either public or private transportation varied.